2020
DOI: 10.3389/fchem.2020.00268
|View full text |Cite
|
Sign up to set email alerts
|

Development of Halide Perovskite Single Crystal for Radiation Detection Applications

Abstract: Preface: Recently, low-cost perovskite single crystals have attracted intensive attention due to their excellent optoelectronic properties and improved stability when compared to polycrystalline films for various applications, such as solar cells (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 72 publications
0
25
0
Order By: Relevance
“…These results indicate that the perovskite sacrifices part of the vertical orientation and makes a more uniform crystallographic orientation, which improved the perovskite film quality and reduced the density of trapped states; this lays a foundation for the high stability of perovskite film. [ 38–40 ] Furthermore, by comparing the q ‐dependent 1D‐GIXRD spectrum around the perovskite (110) peak in Figure 1d, two (110) diffraction peaks at q ≈ 10.0 nm −1 showed similar symmetrical intensity distributions (shown in Figure 1e), which proves that a highly crystalline film with high phase purity was formed in both cases. Besides, as shown in Figure S3 (Supporting Information), the contact angles of bare and BACl:PbI 2 ‐modified SnO 2 films are measured to be 59.6° and 20.7°, respectively.…”
Section: Resultsmentioning
confidence: 79%
“…These results indicate that the perovskite sacrifices part of the vertical orientation and makes a more uniform crystallographic orientation, which improved the perovskite film quality and reduced the density of trapped states; this lays a foundation for the high stability of perovskite film. [ 38–40 ] Furthermore, by comparing the q ‐dependent 1D‐GIXRD spectrum around the perovskite (110) peak in Figure 1d, two (110) diffraction peaks at q ≈ 10.0 nm −1 showed similar symmetrical intensity distributions (shown in Figure 1e), which proves that a highly crystalline film with high phase purity was formed in both cases. Besides, as shown in Figure S3 (Supporting Information), the contact angles of bare and BACl:PbI 2 ‐modified SnO 2 films are measured to be 59.6° and 20.7°, respectively.…”
Section: Resultsmentioning
confidence: 79%
“…Inorganic -ray scintillating materials such as GSO:Ce and LSO:Ge satisfy several of these requirements but often suffer from long decay times (≈40 ns). To this end, hybrid materials [50,138,140] offer short decay times but are generally unstable with a low material density (1 g cm −3 ). Thus, the development of materials that address these challenges is urgently required for further advancing the various imaging technologies.…”
Section: Indirect Gamma-ray Detectorsmentioning
confidence: 99%
“…Gamma‐ray detection plays an important role in a wide range of applications including homeland security, national defense, medical imaging, industrial monitoring, environmental survey, non‐destructive inspection, and basic scientific research. [ 1–4 ] In this regard, semiconductor‐based gamma‐ray detectors are especially appealing due to their high sensitivity and excellent detection efficiency. The high‐purity germanium (HPGe) detectors can offer ultrahigh energy resolution (≈0.3% for 662 keV gamma‐ray).…”
Section: Figurementioning
confidence: 99%
“…In recent years, perovskite materials have emerged as new promising materials for ionizing radiation detection due to their unique advantages, such as suitable bandgap energy, high average atomic number Z, high resistivity, large mobility–lifetime product, and low cost using solution growth methods. [ 1,7,2,3,8 ] In 2016, Yakunin et al. first demonstrated that the solution‐grown formamidinium (FA)‐based hybrid lead halide perovskites, FAPbI 3 , could achieve radiation response to gamma photons.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation